PENGGUNAAN MODEL PEMBELAJARAN NHT UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI KELAS XI IPA SMA ISLAM 1 PRAMBANAN TAHUN PELAJARAN 2009/2010 - Sumarjito, Sumarjito (Bioedukasi Jurnal Pendidikan Biologi, 2011)
This classroom action research aims to determine the increase in student activity, where the learning process-centered and see an increase in student learning outcomes of biology in the 11th science class at The first Prambanan Islamic Senior High School in 2009/2010 academic year with learning models numbered heads together (NHT). The study consisted of two cycles, the first cycle had done by the two meetings held on 26 and May 27, 2010 with material "structure and function of reproductive men and women" and "spermatogenesis, oogenesis and ovulation ". Cycle II carried as many as two meetings held on 1 and June 2, 2010 by presenting "menstruation, fertilization, gestation" and "child - birth, ASI (motherâs milk), contraception, disorders of the reproductive system". Subjects were the 11th grade science class of The first PRAMBANAN ISLAMIC SENIOR HIGH SCHOOL in 2009/2010 academic year on Sleman â Yogyakarta , which amounted Â to thirteen students. Based on this study concluded that the application of learning models numbered heads together (NHT) can make the students active in the learning process, student-centeredÂ  learning (learning that focus on student) and improve learning outcomes.Â Kata kunci: Numbered Heads Together (NHT), Â Hasil Belajar